Using Electrode Made of Carbon Nanotubes and Bismuth Oxide for the Determination of Metal Concentration by Anodic Stripping Voltammetry - Thi Thu Phuong Nguyen; Xuan Gian Trinh; Dao Thi To Uyen (Journal of Chemistry)
We have successfully manufactured a new electrode modified with bismuth oxide (Bi2O3) using carbon nanotubes (CNTs). The electrode was fabricated to detect cadmium (Cd), lead (Pb), and indium (In) by differential pulse anodic stripping voltammetry (DP-ASV). The electrode surface was studied by scanning electron microscopy (SEM), and the reduction and oxidation processes were studied by cyclic voltammetry (CV) techniques. Operational parameters such as electrode size, bismuth concentration, and electrolytic background were optimized. The DP-ASV method used fabricated electrodes with a linear response range from 1.5–20 μg·L−1 with Cd(II) and Pb(II) and 2.5–20 μg·L−1 with In(III); low detection limit (LOD) of 0.22 μg·L−1 with Cd(II), 0.65 μg·L−1 with In(III), and 0.26 μg·L−1 with Pb(II); and good repeatability with relative standard deviations (RSD) of 2.65%, 2.51%, and 3.34% with Cd(II), Pb(II), and In(III), respectively (n = 8). The electrode can be used to test the content of Cd(II), In(III), and Pb(II) in water.